2021
DOI: 10.3390/ani11010137
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Alpha-Ketoglutaric Acid on the Growth and Bone Development of Experimentally Induced Perinatal Growth-Retarded Piglets

Abstract: The effect of alpha-ketoglutaric acid (AKG) supplementation to experimentally-induced, perinatal growth-retarded piglets was examined. Sows were treated with a synthetic glucocorticoid (Gc) during the last 25 days of pregnancy, and after the birth, piglets were randomly divided into three groups depending on the treatment. The Gc/Gc + AKG and Gc/AKG groups born by Gc-treated sows after the birth were treated with Gc or Gc + AKG for 35 days. Significantly lower serum growth hormone, IGF-I, osteocalcin, leptin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Studies have shown that AKG can promote the synthesis of muscle protein (Pierzynowski and Sjodin 1998). In piglets with slow perinatal growth, AKG as an energy donor can promote bone metabolism (Tomaszewska et al 2021). Arginine is a basic component of various proteins, and its precursor can regulate cell proliferation, differentiation, and homeostasis (Bulau et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that AKG can promote the synthesis of muscle protein (Pierzynowski and Sjodin 1998). In piglets with slow perinatal growth, AKG as an energy donor can promote bone metabolism (Tomaszewska et al 2021). Arginine is a basic component of various proteins, and its precursor can regulate cell proliferation, differentiation, and homeostasis (Bulau et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of programming, the metabolic pathways are permanently changed, and the process of adaptation to the new developmental conditions of the fetus must be as quick and efficient as possible, so as not to disturb the entire development of the organism. The effects obtained as a result of the prenatal programming consist in accelerating or inhibiting the development, and somatic and hormonal maturity, which then determine the degree of independence in the postnatal period (Blicharski et al, 2017;Tomaszewska et al, 2020Tomaszewska et al, , 2021. This is especially important at the time of weaning when there is once again a change in the feeding form.…”
mentioning
confidence: 99%